STRATEGY TO DEVELOP BRAND IMAGE NADJANI INDONESIA AS A CARING BRAND FOR COVID19 BY USING “NADJANI COVID19 VACCINATE SALE” PROGRAM - Istisari Lageni; Daniel Handoko; Donny Kurniawan (LPPMP Universitas Bhayangkara Jakarta Raya, 2022)
Covid19 pandemic has changed the world, everything running slow, also with the business. Because of rules about limitation of human traffic in every country. It makes many aviations bankrupt. There also stayed at home rules, business going down, many shopping mall empty, there’s only plentypeople in restaurant, it also happen with fashion business. The needed of fashion, also going down. There are no one can predict how long this pandemic will be going on. So, the society postpone their not so important expens. Most people got scared to travelled or even going out from their house. Stores closed or opened with restricted business hours. Students has to study from home and also workers. It decrased the sales, because people held to buy some stuff which not important. Beside that, because of work from home,workers don’t bought working dress a lot. So, nadjani realized that our business had to changed quickly. To make business run, businessman have to find new ways that adapt from the situation. Some innovative flexible ways have to develop, so in this uncertain situation, business still able to make enough income for the company. Beside making enough income, the new way also can support the brand image keep on their path. At the end, the collaboration of them can make business and brand established.